Komposisi Kimia Minyak Atsiri Daun Cengkeh (Eugenia Caryophyllus) dari Maluku - Vernando Yanry Lameky (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The clove tree, Eugenia caryophylata, Thunb (Syzigium aromaticum, L), (Myrtaceae), grows naturally in the Maluku Islands, Eastern Indonesia, and is cultivated in Tanzania, Madagascar, Sri Lanka, India, Malaysia, Brazil, Jamaica and Guinea. Clove leaf oil from Ambon island is produced by steam distillation. This study aims to determine the main chemical composition of clove leaf oil. The data was obtained from the results of an examination at the Organic Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Pattimura University, namely dry clove leaves weighing 1 kg which had been cleaned of impurities were put in a distilled kettle and tightly closed. Distillation lasts 5 to 7 hours. The mixture of oil and water that comes out of the condenser was collected and allowed to stand for 24 hours. To separate water and oil, anhydrous Na2SO4 is added. Based on the analysis, it was found that the three main chemical components in clove leaf oil were Eugenol 82.43%, β-caryophylene 12.42% and Caryophylene oxide 5.17%.Keywords: Eugenia caryophylata; chemical composition; essential oil ABSTRAK Pohon cengkeh, Eugenia caryophylata, Thunb (Syzigium aromaticum, L), (Myrtaceae), tumbuh secara alami di Kepulauan Maluku, Indonesia Timur, dan dibudidayakan di Tanzania, Madagaskar, Sri Lanka, India, Malaysia, Brasil, Jamaika dan Guinea. Minyak daun cengkeh dari pulau Ambon dihasilkan dengan cara destilasi uap. Studi ini bertujuan untuk mengetahui komposisi kimia utama dalam minyak daun cengkeh. Data diperoleh dari hasil pemeriksaan di Laboratorium Kimia Organik FMIPA Universitas Pattimura yaitu daun cengkeh kering seberat 1 kg yang sudah bersih dari kotoran dimasukkan dalam ketel suling dan ditutup dengan rapat. Penyulingan berlangsung selama 5 hingga 7 jam. Campuran minyak dan air yang keluar dari kondenser ditampung dan dibiarkan selama 24 jam. Untuk memisahkan air dan minyak ditambahkan Na2SO4 anhidrat. Berdasarkan analisis didapatkan tiga komponen kimia utama dalam minyak daun cengkeh adalah Eugenol 82,43%, β-caryophylene 12,42% dan Caryophylene oxide 5,17%.Kata kunci: Eugenia caryophylata; komposisi kimia; minyak atsiri